PROFIL HEART RATE RECOVERY SETELAH EXERCISE MAXIMAL ATLET PELAJAR SIDOARJO PADA CABANG OLAHRAGA DINAMIS - Wulandari, Fifit Yeti (JSES : Journal of Sport and Exercise Science, 2022)
The main objective of this study was to determine the profile of Heart Rate Recovery (HRR) after conducting Exercise Maximal (EM) using speed tests, namely sprints, quantitative research methods while the research sample was 86 male student athletes consisting of 5 athletic athletes, 17 volleyball athletes, 22 hockey athletes, 15 roller skating athletes, 15 beach volleyball athletes and 3 court tennis athletes. the first data collection participants performed a sprint speed test of 30m. Furthermore, HRR is measured using the Polar type H10 tool using the Polar Team monitor system. Furthermore, HRR is recorded at minutes 1,2,3,4, and 5 shortly after doing maximum exercise. Furthermore, by using the paired t-test and friedman's test to see the significance of the difference in values every minute. Furthermore, to get a poor heart rate recovery profile, a calculation of ΔHRR with a maximum heart rate (HR) is carried out. the results showed a significant difference in HRR values of 1, 2, and 3 χ2F (2) = 170.02, p<0.001 using friedman's test. significant differences were also found in hrr values 4 and 5 using paired sample t-test HRR 4 (Mean=104.07, SD=8.838) and HRR 5 (Mean=95.35, SD=7.232) under conditions; t(85)=15.618, p=0.000. furthermore, in order for the difference in HRR to be meaningful, further tests were carried out by looking for Δ HRR1,2,3,4, and 5 with HRmaximal and obtained the values of ΔHRR 1 19.18±6.6, then in order Δ HRR 2: 29.45±7.10, Δ HRR 3: 38.06±6.88, Δ HRR 4:43.72±5.54, and ΔHRR 5:48.44±4.67. In this study, it can be proven that the HRR profile in student athletes can be used as an indicator of athletes' readiness to receive and participate in training programs.